ChemInform Abstract: Use of Trifluoromethyl Groups for Catalytic Benzylation and Alkylation with Subsequent Hydrodefluorination. Issue 22 (12th May 2016) - Zhu, Jiangtao; Perez, Manuel; Caputo, Christopher B.; Stephan, Douglas W.
Abstract: Aryl and alkyl CF3 groups are converted into CH2 ‐aryl fragments upon treatment with arenes in the presence of the reagents/catalyst combination under conditions A).